Sönke Neitzel & Harald Welzer, Soldiers: German POWs on Fighting, Killing, and Dying. Random House, First Vintage Book Edition, USA 2013, 437 σελ. - Vassiliou, Phaidon (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2016)
[Δεν διατίθεται περίληψη / no abstract available]